OPRESI KELOMPOK MINORITAS: PERSEKUSI DAN DISKRIMINASI LGBT DI INDONESIA - Cut Irda Irda Puspitasari (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2019)
This paper discusses the persecution of Lesbian, Gay, Bisexual, Transgender (LGBT) groups in Indonesia. Several cases of persecution against LGBT have become more prevalent in the past few years, as reported by the Indonesian Legal Aid Institute (LBHM) throughout 2017 in Indonesia, there were 973 people who were victims of stigma, discrimination and violence based on sexual orientation, gender identity and expression outside heteronormative binary norms. This paper argues that the persecution of LGBT people in Indonesia occurred because of the oppression of minority groups. The situation is further complicated by the existence of religious views which are increasingly aggressively denominating LGBT groups. This sensitive issue about LGBT is an area of counseling that should be an important concern at this time. Therefore this paper will describe the relationship between LGBT and sensitive counseling on religion and culture.